2019
DOI: 10.5604/01.3001.0013.0645
|View full text |Cite
|
Sign up to set email alerts
|

A closer look at polyunsaturated fatty acids and hypertension

Abstract: Hypertension is the most common chronic cardiovascular disease in adults in all Western societies. Unfortunately, hypertension treatment is still often insufficient and in most countries the majority of patients still have inadequately controlled blood pressure. In recent years, dietary modifications and supplementations, including polyunsaturated fatty acids (PUFA), have attracted considerable interest as a potentially complementary therapy for the treatment of hypertension. The reduction of blood pressure du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The human body does not have a suitable enzyme for the endogenic synthesis of α-linolenic and linoleic acid, due to the lack of desaturases introducing double bonds at the 3 rd and 6 th carbon atoms in the carbon chain. These acids are precursors for the synthesis of long--chain polyene fatty acids such as eicosapentaenoic acid and docosahexaenoic acid [Martynowicz et al, 2019].…”
Section: Determination Of Fatty Acid Profilementioning
confidence: 99%
“…The human body does not have a suitable enzyme for the endogenic synthesis of α-linolenic and linoleic acid, due to the lack of desaturases introducing double bonds at the 3 rd and 6 th carbon atoms in the carbon chain. These acids are precursors for the synthesis of long--chain polyene fatty acids such as eicosapentaenoic acid and docosahexaenoic acid [Martynowicz et al, 2019].…”
Section: Determination Of Fatty Acid Profilementioning
confidence: 99%
“…Recent animal studies [ 80 , 81 ] have demonstrated the beneficial effects of these substances in protecting against chronic kidney disease and its associated complications. Long-chain polyunsaturated fatty acids, particularly n-3 polyunsaturated fatty acids (PUFA n-3), such as alpha-linolenic acid (ALA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA), have been demonstrated to exhibit antithrombotic, hypotriglyceridaemic, and anti-inflammatory effects [ 82 ]. Individuals with CKD have reduced levels of PUFA n-3 in their blood.…”
Section: Nutritional Strategies Focusing On the Gut Microbiota As A N...mentioning
confidence: 99%